Trade Fair for developing countries - M. Busche (Intereconomics, 1968)
It is six years now that the first Import Trade Fair called “Partners of Progress” has been staged in Berlin. Its original form was that of a pure aid to information, but following actual needs, it gradually changed into a commercial trade fair of the developing countries. The number of exhibitors taking part in these fairs, and the growing interest shown by more and more expert visitors, have both made it clear that this kind of trade show has gained a firm position among German trade fairs and specialised exhibitions. We have asked Dr M. Busche, authorised signatory of the Berlin Exhibition Service (Ausstallungs-Dienst Berlin: ADB), about his experiences with the import show, “Partners of Progress”, which is designed exclusively for the promotion of imports from African, Asian, and Latin American developing countries.
Keywords: 330; Interview